Use of technical and economical parameters for evaluating dairy cow ration efficiency - Adduci, Francesco; Labella, Cristiana; Musto, Mauro; D’Adamo, Carmine; Freschi, Pierangelo; Cosentino, Carlo (Italian Journal of Agronomy, 2015)
The aim of this study was the development of a model for evaluating dairy cow ration efficiency. This model took into account technical, metabolic, and economic parameters, which were divided into two main categories: input and output. Feeding (food administered and its nutritional characteristics) was considered as the input parameter. The output indicators were directly or indirectly correlated with feeding, and included: quality and quantity of milk, body condition score, live weight, reproductive parameters, incidence of animal diseases (laminitis), undigested fraction, fecal consistency, feed efficiency (FE), and income over feed cost (IOFC). The model was validated using ten dairy farms located in the northwest of Basilicata. The farms were divided into two groups (A and B) as a function of the urea level in bulk milk. In Group A, the urea level was between 25 and 31 mg/100 mL milk, whereas, in Group B, the range was 21-22.5 mg/100 mL milk. The model showed that the values of reproductive parameters were worse in Group A than in Group B. However, the Group A showed better milk qualitative and quantitative characteristics, such as a high average production per head (28.15 vs 26.93 kg), and a high fat (3.92 vs 3.71%) and protein (3.53 vs 3.37%) content of bulk milk. Moreover, the highest values of FE (1.45 vs 1.35 kg milk/kg dry matter) and IOFC (6.07 vs 5.32 â‚¬) were found in Group A. The model clearly showed that the administration of unbalanced rations, based on the physiological stage of the animals, negatively affected both the qualitative and quantitative characteristics of milk, as well as the reproductive performances. The administration of unbalanced rations for the energy/protein content caused dysmetabolic syndromes, which led to a reduction of both FE and IOFC. This, ultimately, caused a fall in the overall farm profitability.